JALÂL AL-DÎN AL-MAHALLÎ AND JALÂL AL-DÎN AL-SUYUTÎS’ INTERPRETATION METHOD OF THE MUTASYÂBIHÂT VERSE IN TAFSÎR JALÂLAYN - Wildan, T.; Nasution, Ismail Fahmi Arrauf (State Islamic University North Sumatra, 2022)
Abstract: This study aims to determine the research method of al-Mahallî and al-Suyutî on the mutasyâbihât verse in Tafsîr Jalâlayn interpretation, the impact of the mutasyâbihât verse measurement method on understanding Tafsîr Jalâlayn interpretation, and the similarities and differences in the methods used. This research is included in non-empirical research that uses the type of library research and research studies presented in a comparative analytical descriptive manner. Research findings; the methods used by al-Mahallî and al-Suyutî in dealing with mutasyâbihât verses, tawaquf, interruption, and expansion and impact of the mutasyâbihât verse method in Tafsîr Jalâlayn make results as an increase in faith, knowledge in Arabic and interpretation, and facilitate understanding of the control of mutasyâbihât verses. The similarities are the use of methods and interpretations; ta'wîl or bayân. The difference; al-Mahallî is more dominant in the interruption method than the expansion, and al-Suyutî is more dominant in using the expansion method than the interruption.Keywords: mutasyâbihât verse, interpretation, method